'The constant rejections hurt': Skills and personal attributes needed to successfully complete a thesis by publication. Issue 3 (30th May 2019) - Merga, Margaret K.; Mason, Shannon; Morris, Julia E.
Abstract : The thesis by publication (TBP) is an increasingly popular approach to doctoral education that sees candidates publishing their research during their candidature, and including these outputs in their final thesis submission. Responsive to the realities of modern academia, a TBP provides doctoral candidates with opportunities to engage in the scholarly publication process, and to build their research portfolio. As the TBP gains further traction in many fields and countries, there is a need to better understand the skills and attributes needed to complete a TBP successfully. This paper draws on the views of 246 recent doctoral graduates of Australian universities to identify the skills and attributes they felt supported their success. Their responses have implications for the development and refinement of institutional policies and programs that are sensitive to the needs and experiences of doctoral candidates seeking to publish during candidature and create a TBP. As editors, peer‐reviewers, and publishers see a growing influx of papers sole‐ or co‐authored by doctoral candidates in response to the trend toward TBP, they may find themselves involved in supporting students to develop the skills and attributes needed to successfully publish during candidature.